2016
DOI: 10.1089/lap.2016.0161
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Techniques for Totally Laparoscopic Caudate Lobectomy

Abstract: Our experience demonstrated that laparoscopic caudate lobectomy is safe and feasible in selected patients with malignancy in the caudate lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…With the accumulated experience of laparoscopic surgery and the development of laparoscopic devices, an increasing number of studies have reported the safety and feasibility of laparoscopic extended hemihepatectomy [53,54], laparoscopic caudate lobectomy [55,56], laparoscopic hepatoduodenal lymphadenectomy and bilioenteric anastomosis [44,45]. Thus, from a technical perspective, it is obvious that the essential surgical techniques for laparoscopic resection of HC have become more reliable and diverse.…”
Section: Discussionmentioning
confidence: 99%
“…With the accumulated experience of laparoscopic surgery and the development of laparoscopic devices, an increasing number of studies have reported the safety and feasibility of laparoscopic extended hemihepatectomy [53,54], laparoscopic caudate lobectomy [55,56], laparoscopic hepatoduodenal lymphadenectomy and bilioenteric anastomosis [44,45]. Thus, from a technical perspective, it is obvious that the essential surgical techniques for laparoscopic resection of HC have become more reliable and diverse.…”
Section: Discussionmentioning
confidence: 99%
“…In other previous research, total isolated caudate lobectomy was performed by approaching the caudate lobe from the right side of the liver, using the right posterior Glisson pedicle as the anterior border plane of the caudate lobe and reaching the dorsal plane by transecting the parenchyma between the MHV and RHV. There was no mention of the right margin of the caudate lobe [1516]. Although it is known that the anatomy of the caudate lobe is important when performing total caudate lobectomy, the exact locations of the right and ventral margins remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, laparoscopic caudate lobectomy has been performed in only a few experienced centers. Nervertheless, safety and feasibility of this procedure, when performed by experienced surgeons, have been reported by several experienced centers [18][19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 87%
“…Despite these limitations, favorable perioperative outcomes compared to open caudate lobectomy regarding operation time, intraoperative bleeding, and perioperative morbidity have been reported. However, these results are based on the premise that this procedure would be performed by experienced surgeons in laparoscopic liver resection who have profound anatomical knowledge [18][19][20][21][22][23][24]29,39] .…”
Section: Surgical and Oncologic Outcomesmentioning
confidence: 99%